Peningkatan Keterampilan Proses Sains Siswa melalui Context Based Learning - Adam Malik; Endah Kurnia Y; Siti Robiatus S (Jurnal Penelitian & Pengembangan Pendidikan Fisika, 2016)
AbstractRigid object equilibrium is a material that needs well rule and process aplication viewed from tranlation and rotation concept. This phenomenon related to material aplication was much found in daily life. This material instruction requires the development of Saintific Process Skills (SPS). Based on the observation result in MAN Cisewu, this material was considered difficult for the student. The teacher taught the material with mathematical formulas wihthout practicing the saintific process. One of the efforts to solve the problem by using model Context Based Learning (CBL). CBL connects content and contex. It helps the students to be more creative informing concept individually and improves the saintific process skills. Through one grup pretest-posttest design in pre experiment method, the research aims finding out the use of CBL model by using observation sheet and improving students’ saintific process skills measured by multiple choices. The result shows percentage of teacher activity 87,00% (good) and students 85,22% (good). The improvement of students’ saintific process skills showed 0,58% (medium) for N-gain means. The indicator of saintific process skills communicate of the lowest N-Gain (0,06) and the highest N-Gain (0,73) apperead on the indicator of interpretation. Hyphothetical test showed by Wilcoxon match pairs, it is found that Zcount (5,70) > Ztable (1,69). It can be concluded that Context Based Learning can improve saintific process skills of students in material rigid object equilibrium.Keywords: CBL, SPS, rigid object equilibrium AbstrakKeseimbangan benda tegar merupakan materi yang memerlukan penerapan aturan dan proses baik ditinjau dari konsep tranlasi maupun rotasi. Fenomena dan aplikasi yang berkaitan dengan materi ini banyak ditemukan dalam kehidupan sehari-hari Pembelajaran materi ini menuntut pengembangan Keterampilan Proses Sains (KPS). Berdasarkan hasil observasi di MAN Cisewu materi ini dianggap sulit bagi siswa. Guru mengajarkannya dengan cara perumusan matematis dan kurang melatihkan proses sains. Salah satu upaya untuk mengatasinya dengan menerapkan model Context Based Learning (CBL). CBL menghubungkan konten dengan konteks, dapat membantu siswa kreatif dalam membentuk sebuah konsep secara mandiri dan meningkatkan keterampilan proses sains. Melalui metode pre-eksperimen dengan desain one-group pretest-posttest, penelitian ini bertujuan untuk mengetahui keterlaksanaan model CBL yang diamati dengan menggunakan lembar observasi dan peningkatan keterampilan proses sains siswa yang diukur menggunakan soal pilihan ganda. Hasil penelitian menunjukkan persentase keterlaksanaan aktivitas guru 87,00% (baik) dan siswa 85,22% (baik). Peningkatan keterampilan proses sains siswa diperoleh rata-rata nilai N-Gain sebesar 0,58 (sedang). Indikator keterampilan proses sains mengkomunikasikan memperoleh N-Gain terendah (0,06) dan N-Gain tertinggi (0,73) pada indikator menafsirkan. Hasil uji hipotesis menggunakan uji Wilcoxon match pairs diperoleh Zhitung (5,70) > Ztabel (1,69). Dengan demikian dapat disimpulkan bahwa model Context Based Learning dapat meningkatkan keterampilan proses sains siswa pada materi keseimbangan benda tegar.Kata-kata kunci: CBL, KPS, keseimbangan benda tegar